Atp7b-dependent choroid plexus dysfunction causes transient copper deficit and metabolic changes in the developing mouse brain. - Clorissa L Washington-Hughes; Shubhrajit Roy; Herana Kamal Seneviratne; Senthilkumar S Karuppagounder; Yulemni Morel; Jace W Jones; Alex Zak; Tong Xiao; Tatiana N Boronina; Robert N Cole; Namandjé N Bumpus; Christopher J Chang; et al. (PLoS Genetics, 2023)
Copper (Cu) has a multifaceted role in brain development, function, and metabolism. Two homologous Cu transporters, Atp7a (Menkes disease protein) and Atp7b (Wilson disease protein), maintain Cu homeostasis in the tissue. Atp7a mediates Cu entry into the brain and activates Cu-dependent enzymes, whereas the role of Atp7b is less clear. We show that during postnatal development Atp7b is necessary for normal morphology and function of choroid plexus (ChPl). Inactivation of Atp7b causes reorganization of ChPl' cytoskeleton and cell-cell contacts, loss of Slc31a1 from the apical membrane, and a decrease in the length and number of microvilli and cilia. In ChPl lacking Atp7b, Atp7a is upregulated but remains intracellular, which limits Cu transport into the brain and results in significant Cu deficit, which is reversed only in older animals. Cu deficiency is associated with down-regulation of Atp7a in locus coeruleus and catecholamine imbalance, despite normal expression of dopamine-β-hydroxylase. In addition, there are notable changes in the brain lipidome, which can be attributed to inhibition of diacylglyceride-to-phosphatidylethanolamine conversion. These results identify the new role for Atp7b in developing brain and identify metabolic changes that could be exacerbated by Cu chelation therapy.